Beyond diazomethane: Alternative approaches to analyzing non‐esterified fatty acids. Issue 7 (9th February 2015) - Potter, Greg; Budge, Suzanne M.; Speers, R. Alex
<x xml:space="preserve">Abstract</x> In many branches of lipid science, researchers are interested in non‐esterified fatty acid (NEFA) content and composition. For many years, diazomethane was the reagent of choice to selectively derivatize and then detect NEFA due to its highly specific methylation of the carboxylic acid functional group. While the activity of this derivatizing reagent is very defined, it is dangerous and can be difficult to obtain. In this brief review, we have compiled a collection of methods which allow for the detection of NEFA and hydroxy NEFA without the use of diazomethane. We have concentrated on methods that employ three distinct approaches of selective quantification/extraction, purification from total lipids and derivatization techniques.